THE EFFECT OF AUDIO, VIDEO AND MOTIVATION ON STUDENTS’ LISTENING COMPREHENSION ACHIEVEMENT - ROUDHATUL . Jannah; Zainuddin . .; Rahmad . Husein (LINGUISTIK TERAPAN, 2021)
ABSTRACTThe objectives of this study were to explain whether : (1) the students’ achievement in listening comprehension taught by using video was significantly higher than that taught by audio (2) the students’ achievement taught to high motivation significantly was higher than that to students’ low motivation? (3) therewas any significant interaction among teaching media (video and audio) and motivation in listening comprehension achievement. The research design is experimental research by using factorial design 2x2. There were 72 students from MAS YMPI Kota Tanjungbalai as sample of this research. The students were divided into two groups. The first group was treated by using Audio and the second group was treated by using Video. Students’ achievement in listening comprehension was measured by using multiple choice tests. The data were analyzed by applying Two-Ways ANOVA. The result revealed that (1) students’ listening comprehension achievement taught by using video wassignificantly higher than that taught by using audio with Fobservedwas higher than that Ftable at level significance α = 0.05 (Fobserved = 155.7>Ftable = 3.98). (2) There was significant difference of students achievement in listening comprehension with high motivation was taught by using video was higher than that low motivation by using audio with Fobserved is higher than Ftable at the level significance α = 0.05 (Fobserved = 93.4>Ftable = 3.98). (3) There was significance interaction among media (audio and video) and students’ motivation on students’ achievement in listening comprehension with Fobservedwas lower than Ftable at level significance α = 0.05 (Fobserved = 1.2 <Ftable = 3.98). Thus, media (audio and video) and students’ motivation significantly affect the students’ achievement in listening comprehension. Keywords: Audio, Video, Motivation, Listening Comprehension